Emotional intelligence in sport: A ten-year review (2008-2018) - Magrum, E. D.; Waller, S.; Campbell, S.; Schempp, P. G. (International Journal of Coaching Science, 2019)
Evidence indicates emotional intelligence (EI) positively influences performance in leadership, nursing, and business. In sport, preliminary evidence indicates EI positively influences athlete and coach performances. To date, one review has systematically analyzed the literature examining EI's influence on sport up to 2015. Thus, the purpose of this paper is to review the contemporary scholarship examining EI in sport. Pertinent scholarship published between 2008-2018 was searched for, sifted through, and either discarded or included within the review. As a result, fortyfour articles were included and created the foundation for thematic analysis to commence. The analysis revealed four themes relating to EI's influence on psychological skills in sport, coaching, sport performance, and factors transcending sport. Collectively, results indicate EI is advantageous for both athletes and coaches concerning performance, psychological skills, and factors that transcend sport. Furthermore, methodological considerations are discussed, and recommendations are provided to both practitioners and researchers.